6th IEEE/ACIS International Conference on Computer and Information Science (ICIS 2007) 2007
DOI: 10.1109/icis.2007.1
|View full text |Cite
|
Sign up to set email alerts
|

2D Barcode and Augmented Reality Supported English Learning System

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(33 citation statements)
references
References 8 publications
2
28
0
3
Order By: Relevance
“…Alan yazında Magicbook, Zooburst, LearnAR.org, Aurasma gibi genel amaçlı AG uygulamalarının yanı sıra, farklı bilim dallarında araştırmacıların alana özgü geliştirdikleri AG uygulamalarının incelendiği çalışmalar da bulunmaktadır. Örneğin biyoloji alanında, iç organlar, kemikler, hayvanlar; kimya alanında, atomun yapısı, molekül şekilleri; coğrafya alanında, güneş sistemi, gezegenler, dünyanın katmanları; geometri alanında, katı cisimler; fizik alanında, optik ve manyetizma konularıyla ilişkili geliştirilmiş AG uygulamaları ve bu uygulamalar kullanılarak gerçekleştirilen araştırmalar yer almaktadır (Shelton ve Hedley, 2002;Chen, 2006;Liu, Tan ve Chu, 2007;Dünser, Walker, Horner ve Bentall, 2012;İbili, 2013).…”
unclassified
“…Alan yazında Magicbook, Zooburst, LearnAR.org, Aurasma gibi genel amaçlı AG uygulamalarının yanı sıra, farklı bilim dallarında araştırmacıların alana özgü geliştirdikleri AG uygulamalarının incelendiği çalışmalar da bulunmaktadır. Örneğin biyoloji alanında, iç organlar, kemikler, hayvanlar; kimya alanında, atomun yapısı, molekül şekilleri; coğrafya alanında, güneş sistemi, gezegenler, dünyanın katmanları; geometri alanında, katı cisimler; fizik alanında, optik ve manyetizma konularıyla ilişkili geliştirilmiş AG uygulamaları ve bu uygulamalar kullanılarak gerçekleştirilen araştırmalar yer almaktadır (Shelton ve Hedley, 2002;Chen, 2006;Liu, Tan ve Chu, 2007;Dünser, Walker, Horner ve Bentall, 2012;İbili, 2013).…”
unclassified
“…The Group B less paid attention to the materials being taught compared to the participants in Group A, because the AR contents created an interactive environment to boost participant's interest in learning. Many research studies have found a similar positive effect on learner's motivation because of AR (Di Serio, Ibáñez, & Kloos, 2013;Liu, Tan, & Chu, 2007;Medicherla, Chang, & Morreale, 2010).…”
Section: Discussionmentioning
confidence: 71%
“…Because of the characteristic of interactive and augmented virtual object in real scene, it provides the user with an impressive experience. By equipping with the mobile and wireless devices, AR now has many intriguing applications in entertainment and education [4,5,6].…”
Section: Introductionmentioning
confidence: 99%